Renewable Energy Development in Indonesia From New Normal to Better Normal: Environmental Law Perspectives - Adharani, Yulinda; Nurlinda, Ida; Siswandi, Gusman; Priyanta, Maret; Salsabila, Rewita (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2023)
The COVID-19 pandemic has changed many aspects of human life worldwide. This virus makes people aware of the importance of the environment and the relationship between humans and the environment. One of the awareness is the transition from fossil energy to renewable energy. This article aims to explore the opportunities to develop renewable energy in Indonesia from an environmental law perspective and to reduce the obstacle in energy utilization to advancing renewable energy development.  To achieve the aims, the writer uses the doctrinal method. This research adopted a qualitative research method to conduct the research objectives of this study. This article describes the theories of environmental law that grow and develop from human relations. The environment has a vital role in encouraging human behaviour that supports a better normal life that is more harmonious with the environment.  The environmental phenomenon caused by the COVID-19 pandemic is triggering the transition from fossil energy to renewable energy, especially in Indonesia. The Indonesian government should ratify regulations related to renewable energy immediately to reduce the obstacles to renewable energy development, such as environmental problems.DOI: https://doi.org/10.22304/pjih.v10n3.a7